A mentalization-based approach to common factors in the treatment of borderline personality disorder. (June 2018) - Bateman, Anthony; Campbell, Chloe; Luyten, Patrick; Fonagy, Peter
Highlights: Idea of common factors supports a dimensional conceptualization of personality disorders. Personality disorder can be considered, in part, as maladaptive communication. Treatment needs to address interpersonal and social communication systems to establish therapeutic change. Opening of epistemic trust via therapy allows for social learning outside treatment. Abstract : In this paper we conceptualize borderline personality disorder as a disorder of mentalizing, social cognition, and loss of resilience. Several treatment approaches are effective, and meta-analyses suggest that there are few substantive differences in effectiveness between them and between specialized and non-specialized approaches. We propose that these findings arise because of shared mechanisms of change, congruent with current thinking both about the existence of a general 'p' factor of psychopathology and a reconceptualization of personality disorders as involving a lack of resilience resulting from problems with epistemic trust and salutogenesis, the capacity to derive benefit from the social environment. Effective treatments share the characteristics of consistency, coherence and continuity, qualities particularly relevant to borderline personality disorder. They create the conditions for the reopening of epistemic trust, an essential component in therapeutic change, as it enables the individual to use the experience of being mentalized, to learn mentalizing of others, and then apply and develop these experiences in day-to-day life, which is the basis for meaningful therapeutic change.